The Effect of Influencer Popularity on Purchase Decisions Among Gen Z Consumers: Case Study of Scientific Skincare Products - Fitriasari, Dessy; Riyoko, Sisno; Roosdhani, Mohamad Rifqy (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
The Influence of Influencer Popularity, Social Media Engagement, and Customer Trust on Purchase Decisions for Skintific Skincare Products Among Generation Z. This study aims to analyze the impact of Influencer Popularity, Social Media Engagement, and Customer Trust on the Purchase Decision of Skintific skincare products among Generation Z consumers. Using a quantitative approach with a survey method, data were collected from 190 respondents, with 162 valid responses analyzed using SmartPLS 4.0. The results indicate that Influencer Popularity positively and significantly impacts Social Media Engagement (coefficient = 0.755; p = 0.000) and Customer Trust (coefficient = 0.797; p = 0.000). However, its direct effect on Purchase Decision is insignificant (coefficient = -0.006; p = 0.962). In contrast, Customer Trust positively and significantly influences Purchase Decision (coefficient = 0.550; p = 0.000), as does Social Media Engagement (coefficient = 0.387; p = 0.001). Mediation testing reveals that Influencer Popularity indirectly influences Purchase Decision through Customer Trust (coefficient = 0.438; p = 0.000) and Social Media Engagement (coefficient = 0.292; p = 0.000). The R-Square values indicate a strong model fit, with: Purchase Decision (R² = 0.798), Customer Trust (R² = 0.635), and Social Media Engagement (R² = 0.570). These findings confirm that influencer popularity alone is insufficient to drive purchase decisions without the presence of customer trust and social media engagement. Therefore, Skintific's marketing strategy should focus on strengthening Customer Trust and enhancing Social Media Engagement to influence consumer purchase decisions effectively.